2021
DOI: 10.3389/fmats.2021.803871
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters Exert Bactericidal Activity and Enhance Phagocytosis of Macrophage Mediated Killing of Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum is a typical periodontal opportunistic pathogen that contributes to inflammatory diseases at oral or extra-oral sites. The emergence of antibiotics resistance calls for a substitute therapeutic strategy to control bacterial infections effectively. In addition, macrophage is an essential part of host defense against microorganism invasion in vivo. Herein, we synthesized gold nanoclusters (AuNCs) as potent antibacterial material to kill F. nucleatum through bactericidal behavior and pro-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…6-mercaptohexanoic acid (MHA)-protected AuNCs were synthesized by one-pot reduction of sodium borohydride (NaBH 4 ), as described in previous studies [ 27 , 30 ]. The structure of AuNCs were characterized using a Lambda 25 UV/Vis Spectrophotometer (PerkinElmer, Waltham, MA, USA) and Nicolet iS500 Fourier Transform Infrared (FTIR) Spectrometer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…6-mercaptohexanoic acid (MHA)-protected AuNCs were synthesized by one-pot reduction of sodium borohydride (NaBH 4 ), as described in previous studies [ 27 , 30 ]. The structure of AuNCs were characterized using a Lambda 25 UV/Vis Spectrophotometer (PerkinElmer, Waltham, MA, USA) and Nicolet iS500 Fourier Transform Infrared (FTIR) Spectrometer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The regulation of macrophage antimicrobial capabilities primarily involves the modulation of reactive oxygen species (ROS) and the modulation of phagocytic activity. In a study, Chen et al [ 154 ] created gold nanoclusters (AuNCs) as antibacterial materials for the treatment of periodontitis. The findings demonstrated that AuNCs boosted the antibacterial impact against Fusarium in vitro by inducing excessive ROS generation, and that AuNCs promote the phagocytosis of macrophages to F. nuclearum.…”
Section: Biomaterials Regulate Macrophage Polarizationmentioning
confidence: 99%
“…[4][5][6] Most affected has been cancer treatment due to the development of a variety therapeutic agents designed with molecular precision for the treatment of specific cancer genotypes. 7 Additionally, advances in diagnostics and treatment of, e.g., reproductive diseases, 8 Alzheimer's, 9 infectious disease, 10 cardiovascular disease, 11 viral diseases, 12 chronic inflammation, 13 and neurodegenerative diseases 14 have showcased the utility of nanomedicine in a broad range of diseases. At its core the advantage of nanomedicine lies in the tunability of nanomaterials which allow for highly versatile and multifunctional therapeutic agents, often referred to as personalized medicines (Fig.…”
Section: Introductionmentioning
confidence: 99%